Bioactive Compund Profile of Muntingia Calabura Leaf Extract with Different Polarity Solvent - Elvian Indah Nilamsari; L. Hartanto Nugroho; Sukirno Sukirno (Syntax Corporation, 2023)
The pursuit of bioactive compounds from natural sources for potential pharmaceutical and therapeutic applications remains a prominent focus of scientific investigation. Among the myriad of botanical treasures, M. calabura, colloquially known as the Jamaican cherry or strawberry tree, stands as an intriguing candidate, owing to its extensive historical utilization in folk medicine across diverse cultures. This study aimed to comprehensively characterize the bioactive compound profile of M. calabura leaves by employing a spectrum of solvents with varying polarities for extraction. The choice of solvent during extraction plays a pivotal role in determining both the types and quantities of compounds obtained from plant material. Our methodology encompassed cutting-edge analytical techniques, notably gas chromatography-mass spectrometry (GC-MS), to unravel the intricate chemical composition of the extracts derived from M. calabura leaves. Moreover, we scrutinized the potential influence of solvent polarity on extraction efficiency and subsequent bioactivity of the isolated compounds. Our findings underscore the profound impact of solvent selection on the repertoire of bioactive compounds extracted from M. calabura leaves. Polar solvents exhibited a proclivity for extracting compounds of higher polarity, while non-polar solvents favored the extraction of less polar constituents. The identification of prominent bioactive compounds within these extracts encompassed delta-tocopherol, 7-(Î³,Î³-dimethylallyloxy)flavanone, Wogonin, Neophytadiene, Octadecanoic acid, and Hexatriacontane, each with its own distinctive pharmacological significance. This study thus illuminates the critical role of solvent polarity in optimizing extraction processes and maximizing the therapeutic potential of M. calabura. The insights gleaned from this investigation not only contribute to our understanding of natural product chemistry but also hold the promise of inspiring the development of novel pharmaceutical agents and therapeutic interventions with wide-ranging applications.